Optimum portfolio formation analysis with Single-index modelson lq 45 shares for the period 2006-2010 - Almira Harmayati (Indonesia Auditing Research Journal, 2022)
Stock is the type of investment with the high risk high return that is having the high risk but could produce the hight profit as well. Stock portfolio is a collection of shares that are owned by an investor. Optimal stock portfolio will maximize the value of expected return and minimized the risk by combining some stocks with the right proportions. The method used in this research is the Single Index Model. The Single Index Model is a method in which an issuer's stock return has a linear relationship with the market return. The main purpose of this research is to investigate and analyze the portfolio of expected return and optimal risk portfolios based on the Single Index Model. The research results showed there were seventeen stocks with a cut-off point (C*) 0.024365. Optimal portfolio is formed by the seven stocks that have returned the excess beta (ERB) is greater than the cut-off point. Bukit Asam Coal Mine(PTBA), Astra Agro Lestari (AALI), United Tractors (UNTR), State Gas Company (PGAS), Indofood Sukses Makmur (INDF), Holcim Indonesia (SMCB), and Astra International (ASII) with excess return to beta (ERB) of 4.31%, 3 , 37%, 3.21%, 2.94%, 2.85%, 2.63% and 2.56%. The proportion of seven shares of the fund is 29.42%, for PTBA 15.93% for Aali, 16.74% for UNTR, 9.86% for PGAS, 9.71% for INDF, 7.29% 2.63% and 2.56%. The proportion of seven shares of the fund is 29.42%, for PTBA 15.93% for Aali, 16.74% for UNTR, 9.86% for PGAS, 9.71% for INDF, 7.29% 2.63% and 2.56%. The proportion of seven shares of the fund is 29.42%, for PTBA 15.93% for Aali, 16.74% for UNTR, 9.86% for PGAS, 9.71% for INDF, 7.29%